Female with Ankylosing Spondylitis from the 7th–6th century BCE Lori Berd burial (Armenia) - Khudaverdyan, Anahit Yu.; Devejyan, Seda H.; Davtyan, Ruben H.; Yengibaryan, Azat A.; Hovhanesyan, Arshak A.; Vardanyan, Shota A. (Anthropological Review, 2021)
A female skeleton from the Lori Berd archaeological cemetery, located near the city of Stepanavan (Lori Province of Armenia) is described. Palaeopathological analysis revealed a variety pathology (ankylosis of the sacroiliac joints, ankylosis of the vertebrae, syndesmophytes, ankylosed of the costovertebral and costotransverse joint fusions, kyphosis, lordosis, fracture of the anterior inferior iliac spine and traumatic lesions). This paper reports a new case of ankylosing spondylitis in a skeleton and a differential diagnosis performed to determine the etiology of the condition. The vertebral bodies remodel and together with the associated syndesmophytes form a continuous, smooth bone surface that is sometimes referred to as “bamboo spine”. In this skeleton changes in the spine, ribs, the sacrum, acetabulum, head of the femur and greater trochanter, as well as the anterior inferior iliac spine are typical of ankylosing spondylitis in advanced stage. Addtionally, there were signs of a traumatic death with injuries sustained to the scapula and vertebra. Using osteological markers in combination with the reconstruction of the archaeological context, the burial pattern suggests that the pathology the female suffered was likely due to her physical deficiencies.